The Symbiodiniaceae and Bacterial Dynamic Composition of the Coral Echinopora gemmacea on Wuzhizhou Island - Zhuoran Li; Yushan Li; Wentao Zhu; Xiangbo Liu; Rou-Wen Chen; Aimin Wang; Xiubao Li (Journal of Marine Science and Engineering, 2023)
Coral’s susceptibility to bleaching is determined by the strength of the intricate mutual relationships among coral symbionts. However, there is limited knowledge about how the symbiotic members of the scleractinian coral Echinopora gemmacea respond to changes in their surrounding environmental conditions. In this study, we conducted a survey of seawater characteristics in the south and north zones of Wuzhizhou (WZZ) Island, measured symbiotic microalgal density and chlorophyll-a content in the corals, and performed metabarcoding of the Symbiodiniaceae and bacteria communities within coral tissue. Our findings demonstrated that the seawater in the north zone of WZZ Island had higher levels of turbidity, temperature, salinity, and dissolved oxygen content compared to the south zone. This indicated that the corals in the two zones were subjected to distinctive environmental conditions. Analysis of the Symbiodiniaceae composition revealed that Cladocopium sp. C1 and Cladocopium sp. C17 were the dominant species in the southern E. gemmacea, whereas Durusdinium sp. D1a and Cladocopium sp. C17 prevailed in the northern E. gemmacea. Consequently, symbiotic microalgal density and chlorophyll-a content were diminished in the northern E. gemmacea. Furthermore, correlation network analysis revealed the presence of intricate bacterial interactions that potentially mediate coral’s adaptation to environmental stress. This study provides insights into the differences in symbiotic members, including Symbiodiniaceae and bacteria, within E. gemmacea, and contributes to fundamental knowledge for coral conservation efforts.